KOMPARASI PERMUKIMAN DESA ADAT TENGANAN PEGRINGSINGAN DENGAN DESA ADAT TENGANAN DAUH TUKAD DI KARANGASEM BALI - Ida Bagus Made Adi Yasa Adnyana; Ni. G. A. Diah Ambarwati Kardinal; I Made Gde Sudharsana (Pranatacara Bhumandala: Jurnal Riset Planologi, 2021)
This study aims to compare the pattern of residential space and the characteristics of traditional yard pattern in Tenganan Pegringsingan village with Tenganan Dauh Tukad village This research is important to do to make a contribution in the field of regional and urban planning, especially in understanding the comparison of settlement patterns in traditional Balinese traditional villages. The research method used in this thesis is a deskriftif comparative research method. Comparative research method is research that compares two or more symptoms, where in studying it requires primary data or field research as well as secondary data or library materials. The results showed that the Tenganan Pegringsingan Traditional Village and the Tenganan Dauh Tukad Traditional Village have relatively similar settlement space patterns and yard pattern characteristics, there is only a slight difference, one of which is the concept of hulu teben. The concept of hulu teben Traditional Village of Tenganan Pegringsingan is oriented towards the north and the south, where the north is considered a sacred zone while the south is considered a dirty zone. The concept of hulu teben Traditional Village of Tenganan Dauh Tukad is oriented towards the east and the west, where the eastern part is considered a sacred zone while the western part is considered a dirty zone.